Predictive genetic testing for BRCA1/2 in a UK clinical cohort: three-year follow-up - Foster, C (Nature Publishing Group, 2007)
This prospective multicentre study assesses long-term impact of genetic testing for breast/ovarian cancer predisposition in a clinical cohort. Areas evaluated include risk management, distress and insurance problems 3 years post-testing. Participants are adults unaffected with cancer from families with a known BRCA1/2 mutation. One hundred and ninety-three out of 285 (70% response) participants at nine UK clinical genetics centres completed assessments at 3 years: 80% female; 37% carriers of a BRCA1/2 mutation. In the 3 years, post-genetic testing carriers reported more risk management activities than non-carriers. Fifty-five per cent of female carriers opted for risk reducing surgery; 43% oophorectomy; and 34% mastectomy. Eighty-nine per cent had mammograms compared with 47% non-carriers. Thirty-six per cent non-carriers ⩾50 years did not have a mammogram post-test. Twenty-two per cent male carriers had colorectal and 44% prostate screening compared with 5 and 19% non-carriers respectively. Seven per cent carriers and 1% non-carriers developed cancer. Distress levels did not differ in carriers and non-carriers at 3-year follow-up. Forty per cent of female carriers reported difficulties with life and/or health insurance. Given the return to pre-test levels of concern among female non-carriers at 3 years and a substantial minority not engaging in recommended screening, there appears to be a need to help some women understand the meaning of their genetic status.